Are scientific revolutions predetermined? Critical appraisal of wojciech sady’s struktura rewolucji relatywistycznej i kwantowej w fizyce (The structure of the relativistic and quantum revolution in physics) - Sepetyi, D. P.; Сепетий, Дмитро Петрович (My University, 2023)
In his book Struktura rewolucji relatywistycznej i kwantowej w fizyce (The Structure of the Relativistic and Quantum Revolution in Physics, 2020), Wojciech Sady presents his vision of the two greatest scientific revolutions in the 20th century. The book provides an illuminating account of the way these revolutions proceeded and strongly supports the thesis that, contrary to Thomas Kuhn’s famous suggestions, the revolutions involved no breaches in the continuity in scientific development but progressed in an evolutionary (although swift) step-by-step way, and were products of collective interactive processes in the scientific community rather than individual achievements of geniuses. On the other hand, it makes a number of controversial claims. In this article, I contest Sady’s claims that new scientific theories (including the most revolutionary ones) logically follow from the theoretical and experimental knowledge already available (the Entailment thesis) or, at least, their emergence is necessary, inevitable, given the available knowledge, the thought style of the scientific community, and some minimally necessary conditions for the development of science (the Necessitation thesis), and that the role of extra-logical and extra-empirical factors, that can be designated as “creative imagination,” in the development of science is either negative or neglectable.
Keywords: scientific revolution; relativity; quantum mechanics; underdetermination; imagination